Double aorta artifact in sonography – a diagnostic challenge - Robert Hadzik; Przemysław Bombiński; Michał Brzewski (Journal of Ultrasonography, 2017)
The double aorta artifact was described and studied thoroughly twenty-five years ago. Despite this, it is still not commonly known today and can cause diagnostic difficulty. Total aortic duplication can be considered an anatomic defect whilst partial duplication mimics aortic dissection. In the literature, this artifact has been compared with a very rare anomaly, i.e. the occurrence of two aortas in one patient. Currently, however, the differentiation of this artifact from abdominal aortic dissection seems to be of greater significance. The double aorta image occurs when ultrasound waves encounter prismatic fat tissue of the anterior abdominal wall. This artifact is more frequently observed in children and athletic young adults since the structure of this anatomic region in these individuals is conductive to the occurrence of this phenomenon. Moreover, it can be observed more often when curved transducers are used. Due to all these factors, an ultrasound beam undergoes greater refraction and make the artifact clearer. This phenomenon is usually easily recognizable and avoidable, but it sometimes might cause diagnostic difficulty. Obtaining an image of double abdominal vessels on ultrasound examination in transverse sections requires further inspection of the aorta in a different (sagittal) plane. This is not always possible due to poor patient preparation for scanning. Symmetrical flow on Doppler sonography is a typical feature of this artifact. Finally, magnetic resonance imaging or computed tomography can be considered to rule out a pathology.